Evaluasi Kesuksesan Implementasi Sistem Open Public Access Catalog Dengan Delone and Mclean Model Pada Perpustakaan Universitas Brawijaya - Alpia Pentidari; Aditya Rachmadi; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Open Public Access Catalog (OPAC) is one of the systems used and utilized by the library of Brawijaya University to provide information related to the availability and collection of books owned by the library. The purpose of this study was to determine the success of the implementation of the Open Public Access Catalog (OPAC) system in the library of Brawijaya University using Delone and Mclean Model. Delone and Mclean Model consists of six variables, namely system quality, information quality, service quality, use, user satisfaction and net benefits. The population in this study was obtained from the number of active students of Brawijaya University as users of the OPAC system of 57.975 people. The data obtained from this study were obtained from questionnaires and by using the stratified purposive sampling technique, then obtained a sample of 113 respondents. The results obtained in this study are in the condition of each variable in the Delone and Mclean Model. system quality, use, user satisfaction and net benefits are in the high category while information quality and service quality variables are in the high enough category. From the results obtained, it is necessary to prioritize improvements in the indicators possessed by the Delone and Mclean Model variables with an average percentage of each indicator that is below the average percentage of the overall indicator.